z-10(z+1)=8(2-3z)+1

Simple and best practice solution for z-10(z+1)=8(2-3z)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-10(z+1)=8(2-3z)+1 equation:



z-10(z+1)=8(2-3z)+1
We move all terms to the left:
z-10(z+1)-(8(2-3z)+1)=0
We add all the numbers together, and all the variables
z-10(z+1)-(8(-3z+2)+1)=0
We multiply parentheses
z-10z-(8(-3z+2)+1)-10=0
We calculate terms in parentheses: -(8(-3z+2)+1), so:
8(-3z+2)+1
We multiply parentheses
-24z+16+1
We add all the numbers together, and all the variables
-24z+17
Back to the equation:
-(-24z+17)
We add all the numbers together, and all the variables
-9z-(-24z+17)-10=0
We get rid of parentheses
-9z+24z-17-10=0
We add all the numbers together, and all the variables
15z-27=0
We move all terms containing z to the left, all other terms to the right
15z=27
z=27/15
z=1+4/5

See similar equations:

| 2-5x=-2x-7 | | 9x+9x=19x-4x | | (x*7)+(+1*8)+(-2*2)=0 | | x+3=7-4+x | | -8x-10=-4x+2 | | |x-3|+|3x+5|=5 | | -32=3u-11u | | 14x+13x=11x+16x | | 15y-30=18 | | 17x=10x+7x | | 5-x=19+7x | | 6+x=8+x-1 | | 20-x=10+10 | | |2x+3|=|5x-3| | | (2x+1)(3x-2)+5x(2x+1)=0 | | 25x=32x-7x | | 5^n=48828125 | | (x+4/2)(x-1/8)=x+3/4 | | 5x-5=3(4-1 | | |2x=3|=|5x-3| | | 4x+9-2x+5=9x-4+6x-8 | | x-9=10,2 | | -8*x/2=-20 | | (x-3)(6x+9)=0 | | 10/3=x^2-x | | x—18=23 | | 1/2d=5/6 | | 7*a/3=5 | | (2x+11)(x-5)=2x^2+75 | | -1-4x=-x+5+4x-4x | | 0.5^x=0.04 | | 48-2(a+3)=64 |

Equations solver categories